Wave One and One Shape Files: Survival in Severely Curved Artificial Canals (Global Journal of Medical Research, 2014)
Nickel-titanium rotary instruments are preferred for their excellent flexibility, superelasticity and improved cutting efficiency but they can separate unexpectedly, especially in curved canals. Instrumentation with WaveOne and One Shape files was performed on 200 artificial canals divided in four equal groups. Glide path was created with PathFiles and G-files. Average lifespan and survival rate of the shaping files were tested, before and after a glide path creation. Average lifespan of WaveOne and One Shape files without a creation of a glide path was 10.25±2.50 canals and 4.1 (±1.37) canals, respectively and after the creation of a glide path -17.50±2.12 canals and 4.6 (±1.30) canals. Average lifespan and cumulative survival of the tested files revealed significant difference. WaveOne files showed significantly higher resistance to fracture compared with One Shape files. Lifespan and survival rate of tested files increased after the creation of a glide path. Reciprocal motion increases significantly instruments life.
Keywords: nickel-titanium instruments; waveone; one shape; pathfiles; g-files; glide path; lifespan; cumm-ulative survival; continuous rotation; reciprocating m